THE APPLICATION OF GLYROXYL AS DECONTAMINATION AND DISINFECTION AGENT FOR THE PRESERVATION OF FISHERIES PRODUCT - Y.S. Darmanto; Tri Winarni Agustini (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Fisheries products are regarded as perishable food. Fresh prawn is one of the most valuable fisheries products and its demand increases especially in developed countries. Handling and preserving of fresh prawn has been investigated to keep the quality. Glyroxyl has been successfully used as decontamination agent in the fish sector in the Netherlands. Apart from its use as decontamination agent, glyroxyl has been proved to be an efficient disinfectant. Due to its safe character, it is allowed to put glyroxyl in foodstuff directly, provided that the prescribed concentration is respected. This study is aimed to investigate the effect of different concentration of glyroxyl (0, 0.3 and 0.5%) on the preservation of fresh prawn. The sample used was white shrimp prawn (Penaeus monodon). The samples were soaked in glyroxyl solution with different concentrations. The analyses were conducted for organoleptic, Total Plate Count (TPC) and E. coli at 0 and 3 days storage at refrigerated temperature. The results showed that the use of glyroxyl solution (0%, 0.3% and 0.5%) has no effect on the organoleptic parameters of the sample (appearance, color and flesh). However, after 3 days of storage the effect of glyroxcyl became apparent especially for 0 % glyroxcyl treatment. The number of E. coli showed that application of glyroxyl could prevent the growth of E. coli and reduce the number of E. coli in the samples. In addition the E. coli obtained was less than number < 3 / < 3 in all samples after 3 days storage. Increase in glyroxyl concentration resulted in the decrease of bacterial number (TPC) both for 0 and 3 days storage